The Relationship Between Nurses' Caring and the Anxiety of Inpatients at the Koto Baru Community Health Center, Dharmasraya Regency - Vella Deli Fitri Ramadani; Astuti Ardi Putri; Erma Erfiana (STIKES Hesti Wira Sriwijaya, 2025)
Introduction: Caring is a behavior or action taken to provide a sense of physical and emotional security to others in a sincere manner. Caring is central to nursing practice, requiring nurses to be more concerned with their patients. The aim of this study was to determine the relationship between nurses' caring and the anxiety of inpatients at the Koto Baru Dharmasraya Community Health Center. Methods: This research is a quantitative study with an analytical survey design using a descriptive approach. The population was all 144 patients who underwent medical check-ups at the Koto Baru Community Health Center between August and December. A sample of 35 individuals met the inclusion and exclusion criteria. The sampling technique used was accidental sampling. Results: The results of the study, namely univariate analysis, obtained 25 (71.4%) respondents with sufficient caring and 25 (71.4%) respondents with mild to moderate anxiety. Bivariate analysis using the Chi-Square test showed a relationship between nurse caring and patient anxiety with a P value of 0.000 ≤ 0.05. Conclusion: Suggestions are expected for the future so that nurses can improve caring behavior and reduce patient anxiety at the Koto Baru Community Health Center.